COMPARATIVE ASSESSMENT OF MORPHOMETRIC AND GROWTH CHARACTERISTICS OF AFRICAN CATFISH (CLARIAS GARIEPINUS) IN CULTURED AND WILD HABITATS IN ZARIA, NIGERIA - Atawodi, Joy Cecilia; Kawo, Abdullahi Hassan; Abdullahi, Bukar Alhaji; Yola, Idris Ado (FUDMA JOURNAL OF SCIENCES, 2025)
This study provides an assessment of the condition factor, length-weight relationship, and sex ratio of Clarias gariepinus (Burchell, 1822) in both controlled (cultured) and uncontrolled (wild) habitats within Zaria, Nigeria. As a key species for commercial fisheries and food security, the African catfish plays a vital role in fisheries management. Using standard methods, 360 samples of Clarias gariepinus were collected and subjected to morphometric measurements, including total length (TL) and body weight (W). The condition factor (K) was determined using the formula K = (W/L³) × 100, while the length-weight relationship (LWR) was expressed as W = aLb, revealing allometric growth patterns. Controlled populations exhibited a greater average total length and weight (35.06 ± 5.13 cm, 318.05 ± 146.75 g) compared to their wild counterparts (30.69 ± 7.51 cm, 232.45 ± 154.89 g). The condition factor in both environments was relatively low (<1.00), suggesting possible environmental stress. The sex ratios indicated a slight female predominance in both settings, with ratios of 1.00:1.52 for controlled environments and 1.00:1.47 for wild populations. These results emphasize the need for further research into the environmental factors influencing fish health and growth, providing critical information for optimizing fisheries management and conservation strategies.